Pupils’ involvement in the social networking sites: a case study at Sekolah Menengah Kebangsaan Bukit Rambai, Melaka / Ainul Nadia Abdullah and Nur Illiana Abd Rahaman - Abdullah, Ainul Nadia; Abd Rahaman, Nur Illiana (Faculty of Administrative Science and Policy Studies, 2014)
As the Earth moves into the second decade of the 21st century, one of the major things that arise and use online communities and social networking sites like Facebook and Twitter become popular among online communities with large user populations. According to Madden & Lenhart (2007), a social networking site is a place to online where a user can create a profile and build a personal network that connects him or her to another user by interacting with each other. It demonstrates how the social networking sites are very important in people’s life to connect themselves with the others in the world. In addition, to routinely checking emails, reading daily forums and newspaper following instant message tools, people now also check their social networking profiles by following others’ status changes, updating their profiles or looking at others’ profiles (Mazman & Usluel, 2011). Because the popularity of these networks has arisen, these sites have generated concern among some parents, school officials, and government leaders about the potential dangers posed to young people when personal data is made available in such a public setting.